Pengaruh Kualitas Siakad Terhadap Kepuasan Mahasiswa Dengan Perceived Usefulness Sebagai Variabel Intervening - Yulias Primita Siswanto; Muhammad Firdaus; Supardi Supardi (RELASI : JURNAL EKONOMI, 2021)
The purpose of this research is to measure and test the variables and indicators that influence the success of academic information system (SIAKAD) in universities with STIE Mandala Jember as a case study. Adopting Delone & Mclean IS Success research model, a set of structured questionnaires were distributed to 100 respondents. Exogenous variables include System Quality, Information Quality, Service Quality, and endogenous variables Student Satisfaction. Perceived usefulness variable used as a intervening variable proved it could mediate the quality of information, the quality of system and the quality of services to user satisfaction. Path analysis is employed as analitical technic. The result shows that there is a significant effect on the quality of the system, quality of the information, the quality of the services to the students’ satisfaction. Perceived usefulness variable, can mediate between exogenous variables to endogenous variables. This conclusion support the prediction of many previous researches.This indicates that the model used is not proper because the model is built on the construct of implementation of academic information system onstudents’ satisfaction. Keywords: System Quality, Information Quality, Service Quality, and Perceived Usefulness.